Efektivitas Program Aplikasi IKD dalam Pembuatan e-KTP di Mall Pelayanan Publik (MPP) Kabupaten Sidoarjo - Amalia Pinka Firdaus; Agus Prastyawan (Perspektif Administrasi Publik dan hukum, 2026)
This study aims to analyze the effectiveness of the Digital Population Identity (Identitas Kependudukan Digital/IKD) application program in supporting electronic identity card (e-KTP) services at the Public Service Mall (MPP) of Sidoarjo Regency. The study is motivated by the government's effort to improve population administration services through digital transformation. Although the IKD application has simplified service delivery, its implementation still encounters several challenges, including system disruptions, limited digital literacy among citizens, and insufficient public outreach. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The analysis was based on Duncan's effectiveness theory, which includes the dimensions of goal achievement, integration, and adaptation. The findings indicate that the IKD application program has been reasonably effective in supporting e-KTP services by improving accessibility, reducing service time, and enhancing service quality. However, its effectiveness has not yet reached an optimal level due to technical issues within the application, limited public understanding of digital services, and the need for more intensive socialization and user assistance to maximize the objectives of digital population administration services.